(untitled) (Malden, MA, 2008)
The distinctive relationships between landscape change, habitat fragmentation, and biodiversity conservation are highlighted in this original and useful guide to the theory and practice of ecological landscape design. Using original, ecologically based landscape design principles, the text underscores current thinking in landscape management and conservation. It offers a blend of theoretical and practical information that is illustrated with case studies drawn from across the globe.
Keywords: Landscape protection,Ecological landscape design,Bảo vệ cảnh quan,Thiết kế cảnh quan sinh thái